Rapid Induction of Pulmonary Inflammation, Autoimmune Gene Expression, and Ectopic Lymphoid Neogenesis Following Acute Silica Exposure in Lupus-Prone Mice - Chauhan, Preeti S.; Wagner, James G.; Benninghoff, Abby D.; Lewandowski, Ryan P.; Favor, Olivia K.; Wierenga, Kathryn A.; Gilley, Kristen N.; Ross, Elizabeth A.; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2021)
Occupational exposure to crystalline silica (cSiO2) is etiologically associated with systemic lupus erythematosus (lupus) and other autoimmune diseases. cSiO2’s autoimmune effects in humans can be mimicked chronically in female lupus-prone NZBWF1 mice following repeated exposure to the particle. However, the immediate and short-term effects of cSiO2 in this widely used model of autoimmune disease are not well-understood. In the present study, we tested the hypothesis that a single acute cSiO2 dose triggers early presentation of cellular, histopathological, transcriptomic, and protein biomarkers of inflammation and autoimmunity in lupus-prone mice. Eight-week old female NZBWF1 mice were intranasally instilled once with 2.5 mg cSiO2 or saline vehicle and necropsied at 1, 7, 14, 21 and 28 d post-instillation (PI). Analyses of bronchoalveolar lavage fluid (BALF) and lung tissue revealed that by 7 d PI, acute cSiO2 exposure persistently provoked: i) robust recruitment of macrophages, neutrophils, and lymphocytes into the alveoli, ii) cell death as reflected by increased protein, double-stranded DNA, and lactate dehydrogenase activity, iii) elevated secretion of the cytokines IL-1α, IL-1β, IL-18, TNF-α, IL-6, MCP-1, and B cell activation factor (BAFF), and iv) upregulation of genes associated with chemokines, proinflammatory cytokines, lymphocyte activation, and type I interferon signaling. The appearance of these endpoints was subsequently followed by the emergence in the lung of organized CD3+ T cells (14 d PI) and CD45R+ B cells (21 d PI) that were indicative of ectopic lymphoid structure (ELS) development. Taken together, acute cSiO2 exposure triggered a rapid onset of autoimmune disease pathogenesis that was heralded in the lung by unresolved inflammation and cell death, proinflammatory cytokine production, chemokine-driven recruitment of leukocytes, an interferon response signature, B and T cell activation, and ELS neogenesis. This short-term murine model provides valuable new insight into potential early mechanisms of cSiO2-induced lupus flaring and, furthermore, offers a rapid venue for evaluating interventions against respirable particle-triggered inflammation and autoimmunity.